Chronic mucocutaneous candidiasis and rheumatoid arthritis in autoimmune polyendocrinopathy - Ismael, Dooha K.; Mahmood, Zainab (Indian Journal of Case Reports, 2022)
Chronic mucocutaneous candidiasis is a heterogeneous group of disorders characterized by early-onset chronic recurrent mucocutaneous infections with Candida albicans. It is associated with several endocrinopathies such as hypoparathyroidism, hypoadrenalism, and hypogonadism with or without other autoimmune diseases such as vitiligo, alopecia areata, pernicious anemia, and hepatitis. Here, we describe a case of chronic mucocutaneous candidiasis with polyendocrinopathy with unusual presentations and rheumatoid arthritis.